Synthesis and Characterization of Graphene Oxide. Review 2014-2020 (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
In recent years, graphene oxide has received much attention from researchers. Due to its multiple applications, including heavy metal adsorption, dye adsorption, microwave absorption, photocatalysis, sensing applications, and membrane separation processes, GO can be synthesized using a number of methods. According to Staudenmaier's oxidation methods, graphite oxide is formed by oxidizing graphite with concentrated acids or strong oxidants. The Hummer's method is widely used in the world because it has clearly explained the structure of graphite oxide using a variety of different models, as shown by Dreyer et al. The Lerf-Klinowski model, which is widely used in graphite oxide synthesis, has layers with hydroxyl and epoxy groups in the center and carboxyl groups at the edges. The oxygen groups in graphene oxide give it a hydrophilic character, and active groups contained between the layers give it an internal space of up to 6–12 A°, depending on the amount of water applied. This review highlights the study of the literature from 2014 to 2020 regarding the preparation and characterization of graphene oxide.